A phase change material packaged multifunctional nanoplatform integrating hydrogen peroxide self-supply and photothermal response for boosting synergistic chemodynamic and photothermal therapy - Pang, Kai; Pidamaimaiti, Guligena; Zhu, Yuxi; Sun, Da; Yu, Bingchen; Duanmu, Zheng; Wang, Fu; Wei, Xunbin (New journal of chemistry, 2023)
Chemodynamic therapy (CDT) has received widespread attention due to its selectivity and oxygen independence, and is an emerging therapeutic methodology aimed at converting hydrogen peroxide (H 2 O 2 ) into hydroxyl radicals (&z.rad;OH). Despite the overexpression of H 2 O 2 in solid tumors, the content is too low for efficient CDT. Here, the integration of H 2 O 2 self-supply and photothermal response was achieved using the synthesized nanoparticles, which are CuS/CaO 2 @PCM (phase change material) nanoparticles. After NIR irradiation, the thermo-responsive PCM was melted to precisely release CuS and CaO 2 from nanoparticles. In response to the acidic tumor microenvironment (TME), CaO 2 can produce a large amount of H 2 O 2 to participate in a Fenton-like reaction. In turn, the generated &z.rad;OH induces a series of oxidative damage that triggers apoptosis. Meanwhile, CuS converts photon energy into heat via photothermal therapy (PTT) to enhance the antitumor effect. The in vitro and in vivo therapeutic outcomes demonstrated that CuS/CaO 2 @PCM nanoparticles efficiently generate toxic H 2 O 2 and hyperthermia at the tumor site, thus enabling enhanced CDT and PTT effects. This therapeutic strategy offers a self-amplified synergistic treatment paradigm for tumors. Chemodynamic therapy (CDT) has received widespread attention due to its selectivity and oxygen independence, and is an emerging therapeutic methodology aimed at converting hydrogen peroxide (H 2 O 2 ) into hydroxyl radicals (&z.rad;OH).